Radon Risk and Remediation: A Psychological Perspective - Hevey, David (Frontiers in Public Health, 2017)
Although radon exposure in the home increases the risk of lung cancer, this risk can be managed. However, evidence indicates that testing for radon and subsequent home remediation rates are generally low in many countries. The present perspective outlines some key insights from psychological science that might account for sub-optimal radon protection. Psychological aspects of how the health risks posed by radon are perceived and managed are outlined. There is need to consider radon risk perception in terms of the (a) cognitive and emotional responses to radon and (b) social context in which the radon threat occurs. In addition, the nature of the threat itself is integral to the failure for people to act in response to a radon threat. Finally, the challenges arising from defensive processing of radon threat information are outlined.